Overconfidence & career development - evidence from an online experiment - Holschneider, Julius (2017)
This paper studies the influence of work-experience and professionalism on general overconfidence. An online experiment has been conducted to compare the level of overconfidence between 5 different subject groups of a total sample of 270 individuals from 35 different countries. Socioeconomic control variables have been used to better clarify the unique influence of experience on the overconfidence level. The findings of this quantitative study suggest that even high levels of work experience do not significantly reduce overconfidence. This generates some major implications and tasks for businesses and organizations to be able to reduce the most damaging of existing heuristics.